The Effect of Judo Training on Set-Shifting in School Children. - Lo, Wai Leung Ambrose; Liang, Zhenwen; Li, Wenfeng; Luo, Suying; Zou, Zhi; Chen, Shaozhen; Yu, Qiuhua (BioMed Research International, 2019)
Improving executive functions (EFs) is desirable as they are considered to be critical for academic attainment and mental wellness in children. The aim of this study was to explore the effect of Judo training on the set-shifting function using a spatial task-switching paradigm. Protocol  1 compared the set-shifting ability of Judo players with age-matched healthy individuals. Protocol  2 compared the difference in EFs between children who underwent Judo training (intervention) and age-matched controls. EFs were assessed by a spatial task-switching test. Error rates and response times were analysed using two-way repeated-measures ANOVA. Protocol 1. The group effect on error rates was significant. The trial type × group effect was significant in the Judo group. Error rates in the Judo group were lower in the switch trials than the control group (p = 0.001). No significant group difference was seen in the repeat trials (p = 0.764). Protocol 2. The time × trial type × group effect was significant. Post hoc analysis showed significantly lower error rates by the intervention group on switch trials compared to the control group (p = 0.006). Regular Judo training may potentially be an option for improving EFs in schoolchildren or in populations with executive dysfunction.